Ways out of the WTO's December crisis: How to prevent the open global trade order from unravelling - Laura von Daniels; Susanne Dröge; Alexandra Bögner (Stiftung Wissenschaft und Politik (SWP), 2019)
The World Trade Organization (WTO) is facing the biggest crisis since its inception in 1995. From 11 December, the committee that deals with WTO members' appeals, the Appellate Body, will be left with only one judge. New appointments have been blocked by the United States. This will incapacitate the Body because the minimum requirement for any decision is three judges. What seems to be a mere procedural issue will result in major disruptions for international trade relations and might ultimately lead to the unravelling of the existing global trade order. The EU and like-minded partners have three options to cope with the situation and to safeguard the WTO's role in trade dispute settlement. The EU and its partners could either endure the stalemate while aiming for a broader WTO reform. Or the EU could strive for an alternative appeals mechanism within the WTO, as an interim solution. The third option would be to seek dispute settlements outside of the WTO. None of the options comes without risk of failure since there is uncertainty about the US endgame, and each move could deliver proof for the US that the WTO no longer serves its interests.
Keywords: 320